Pengembangan Multimedia Interaktif Pada Mata Pelajaran Jaringan Dasar - Ikbal, Ahmad; Fatoni, Ahmad (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
This study aims to develop interactive multimedia based on the talking stick learning model approach on the basic network subject for student of tenth grade at Vocational School High NW Kumbung and to find out the feasibility of interactive multimedia based on the assessment of material expert, media expert, and student opinion.This study wasstudy or development (S& D) study adapted from the waterfal development model. There areÂ  5 stages, namely: Communication Phase, Planning Phase, Modeling Phase, Construction Phase, Deployment Phase. The validation was carried out by material expert, media expert. The developed media was tested on 25 students of tenth grade at Vocational High School NW Kumbung.Based on the study that had been done, the result can be obtained from, (1) The validation result conducted by the validator team was media expert validation with an average score of 72% with good category and material expert with an average score of 86,841 with very good category, ( 2) The result of student responses to interactive multimedia material was very feasible with an overall percentage of 83.2%. So, it can be concluded in this study,Â  the development of interactive multimedia using the waterfall model was said to be feasible to use for basic network learning.